2013
DOI: 10.1016/j.jvs.2012.11.040
|View full text |Cite
|
Sign up to set email alerts
|

A single nucleotide polymorphism in the p27Kip1 gene is associated with primary patency of lower extremity vein bypass grafts

Abstract: Objective Factors responsible for the variability in outcomes after lower extremity vein bypass grafting (LEVBG) are poorly understood. Recent evidence has suggested that a single nucleotide polymorphism (SNP) in the promoter region of the p27Kip1 gene, a cell-cycle regulator, is associated with coronary in-stent restenosis. We hypothesized an association with vein graft patency. Methods This was a retrospective genetic association study nested within a prospective cohort of 204 patients from three referral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Outer wall cells respond more to growth factors than inner wall cells and the association between cell growth and graft patency was greater with the outer wall cells 2 . In addition, we have found that the in vitro growth of outer wall cells, but not inner wall cells, is associated with the genotype of the −838C>A p27 Kip1 single nucleotide polymorphism (manuscript in preparation) that is itself associated with peripheral vein graft failure 13 . It is not clear whether the outer wall cells are derived from a smooth muscle cell lineage, but future experiments to determine whether these cells have epigenetic marks indicating smooth muscle lineage, such as H3K4me2 at the MYH11 locus 14 , should be informative.…”
Section: Discussionmentioning
confidence: 97%
“…Outer wall cells respond more to growth factors than inner wall cells and the association between cell growth and graft patency was greater with the outer wall cells 2 . In addition, we have found that the in vitro growth of outer wall cells, but not inner wall cells, is associated with the genotype of the −838C>A p27 Kip1 single nucleotide polymorphism (manuscript in preparation) that is itself associated with peripheral vein graft failure 13 . It is not clear whether the outer wall cells are derived from a smooth muscle cell lineage, but future experiments to determine whether these cells have epigenetic marks indicating smooth muscle lineage, such as H3K4me2 at the MYH11 locus 14 , should be informative.…”
Section: Discussionmentioning
confidence: 97%
“…Despite technological advances and improvements in surgical techniques, the precise factors that determine whether a vein graft adopts an adaptive, outwardly remodeling phenotype, versus an occlusive phenotype, are largely unknown. A SNP of the p27 kip1 gene, a key cell-cycle inhibitor, has recently been associated with improved revascularization outcomes following both coronary angioplasty and lower extremity vein graft bypass 1, 2 , yet the mechanisms underlying this clinical observation remain undefined. Here we attempted to dissect the gene pathways and networks at play in shaping these divergent outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…and van Tiel et. al., in fact, have identified a single nucleotide polymorphism (SNP) in the promoter region of the p27 kip1 gene that is associated with divergent clinical outcomes following lower extremity vein bypass grafting and coronary artery stenting, respectively 1, 2 . Both clinical studies demonstrated the p27 kip1 -838C>A SNP to be associated with significantly increased rates of clinical success compared to the -838CC and -838CA genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…But rather, intimal hyperplasia develops within a dynamic conduit, molded by hemodynamics, under the influence of systemic and regional factors. Thus inflammation,[22] race,[25] gender,[28] and genetics[29] can act globally on the entire vein graft to influence its adaptation in the arterial circulation. However, should local levels of shear stress and wall tension be impeded from reaching or reestablishing baseline conditions – due to either local environmental conditions, flow disturbances, or intrinsic vein disease - the proliferative intimal reaction would be expected to continue and stenosis to supervene.…”
Section: The Remodeling Of Human Vein Bypassmentioning
confidence: 99%